Istilah Kekerabatan dalam Bahasa Kodi Sumba Barat Daya: Kajian Linguistik Antropologi - Kami, Kanisius; Goro, Stefania Iren; Rato, Daniel Kartono (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe kinship terms in the Kodi language through an anthropological linguistic approach with a focus on the analysis of social structure, culture, and interpersonal relationships of the Kodi community. This type of research is an anthropological linguistic approach with a descriptive qualitative method. The data collected in the form of words and phrases related to kinship terms in the Kodi language were analyzed using the Burling (1970) framework. The analysis was carried out to explore the cultural meaning contained in the language, by referring to the theories of Spredley (1979) and Casson (1981), in order to understand the construction of cultural meaning in the expressions used by informants. Data collection techniques include interviews (speak), as well as recording and note-taking techniques. The results of the study identified kinship terms that are structured based on age hierarchy, namely consanguineous kinship, afinal kinship, and ego-parallel which influence social norms related to respect, politeness, and trust in daily interactions